Assessment of Major Complications in Pregnancy: A Single Center Study - Sheik, Ruksar; P, Manjula. (Asian Journal of Pharmaceutical Research and Development, 2017)
Pregnancy complications in our country are common in spite of a lot of progress made in antenatal care of pregnant women in the recent times. The complications range from simple anemia to ectopic pregnancy. We conducted an observational study in a government maternity hospital where majority of the patients came from rural and impoverished background. The study was done for a period of 6 months during which we had interacted with the patients. The analysis of the results indicated that most of the complications were linked to poverty, ignorance, early pregnancy and non compliance of the medication. Complications could have been easily prevented if the patients had access to healthy, nutritious food and appropriate counseling. Low birth weight newborns were born to the women who were severely anemic. The study showed a strong link between pregnancy complications, low birth weight of newborns and prevalence of anemia in pregnant women.